SAVING UKRAINIAN CULTURAL HERITAGE DURING THE WAR: PRACTICES OF INTERNATIONAL INTERACTIONS - Rohozha, Mariya (Ukrainian Cultural Studies, 2023)
The article deals with the experience of preserving cultural heritage in the armed conflict in Ukraine and international cooperation in this field. The historical reconstruction of the legal protection of cultural heritage is carried out. It is indicated in the article that during the 19th century, international legal bases for the preservation of cultural heritage were actively developed. However, in the 20th century, two world wars brought significant destruction of cultural heritage by all parties of the conflict. And the optimism of the Europeans of the 19th century regarding a civilized attitude to cultural heritage was destroyed, although the work on the creation of international normative documents in the field continued and international organizations were founded that took care of cultural heritage. In the 21st century, the previous trends persist. Such reconstruction can become the context for the Ukrainian situation. To clarify it, the method of situational analysis is used. The situations with the Hryhorii Skovoroda museum in the village of Skovorodinivka in the Kharkiv region and the Ivankiv Local History Museum unfold in time and space and focus the theoretical framework. In the article, the author addresses the problem of the biography of a place, which is relevant in modern social sciences and humanities. Despite objections to anthropomorphization, scholars emphasize the close link of places and human destinies there.Skovorodinivka ceases to be exclusively a place of memory of an outstanding Ukrainian philosopher and becomes evidence of the attitude towards the object of cultural heritage in the current war. The article shows that in Ukraine today, the war is blurring the "battlefield" and military actions are spreading to the territory where the civilian population and cultural heritage sites are located. The striking difference in the attitude towards thecultural heritage of mankind during the military conflicts of the optimistic modern XIX and the postmodernist relativistic XX centuries illustrates the loss of position by modern phenomena. The situation with the Hryhorii Skovoroda museum testifies that today international aid comes for the preservation of the destroyed cultural artifacts. International cooperation is also essential in the issue of digitizing the cultural heritage of Ukraine and creating conditions for its preservation. The article indicates the initiatives of SUCHO (Saving Ukrainian Cultural Heritage Online) and the Vasa Museum, Stockholm, on this path
Keywords: Russian-Ukrainian war; cultural heritage; biography of the place; preservation of cultural heritag